Sleep quality among medical students during third wave of COVID-19 pandemic: A cross-sectional study in Government Medical College Jammu - Mahajan, Richa; Gupta, Rajiv Kumar; Mahajan, Reeha; Gupta, Riya; Langer, Bhavna; Kumari, Rashmi (Indian Journal of Community Health, 2024)
Background: COVID-19 has caused lot of suffering for everyone. Hundreds of thousands of people were affected in all aspects. Increased stress due to the pandemic may affect medical students' sleep quality. The authors aimed to evaluate the sleep quality of medical students during pandemic and relationship, if any, between sleep quality and and socio-demographic variables. Methods: An online survey of medical students was conducted in January 2022, when India was in third wave of pandemic. This cross-sectional study was conducted using the Pittsburgh Sleep Quality Index (PSQI) questionnaire at a tertiary teaching hospital in Jammu, UT, J&K, India. Results: Among 307 participants, mean global PSQI score was 9.91± 3.62 which indicated a poor quality of sleep. Among the component scores, habitual sleep efficiency had the highest score of 2.99± 0.16. Majority (91.53%) of the respondents had a poor sleep quality with global PSQI score >5. Among the socio-demographic variables, alcohol intake and any conflict in the family were found to be statistically significant (p<0.05). Conclusion: Nine out of ten medical students have insufficient sleep, which is a real cause for concern. The authors recommend that stress management (anxiety), lifestyle changes, and sleep training be included in the medical record and updated regularly.